2021
DOI: 10.3389/fnhum.2021.627589
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Anxiety: An Investigation of the Moderating Role of Sex in Performance Monitoring and Attentional Bias to Threat in High Trait Anxious Individuals

Abstract: Anxiety disorders are more predominant in women than men, however there is a lack of understanding as to what neurocognitive mechanisms drive this sex difference. Recent investigation has found a potential moderating role of sex in the relationship between anxiety and the error related negativity (ERN)—a component of error-monitoring that is prevalent in high anxiety individuals—such that females display a positive relationship between anxiety/worry and ERN amplitude. We strove to further explore the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…These specific accuracy requirements were maintained in the flanker task due to the collection of EEG data to measure the error-related negativity (ERN) as part of the larger study. While the EEG/ERN data is not relevant for the scope of this manuscript, additional details regarding this component can be found in previous publications ( Carlson et al, 2021 ; Gilbertson et al, 2021 ; Strand et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…These specific accuracy requirements were maintained in the flanker task due to the collection of EEG data to measure the error-related negativity (ERN) as part of the larger study. While the EEG/ERN data is not relevant for the scope of this manuscript, additional details regarding this component can be found in previous publications ( Carlson et al, 2021 ; Gilbertson et al, 2021 ; Strand et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…We acknowledge that our sampling is not a gender-balanced sample and that our results might skew to one gender, “female.” Past studies showed a gender difference in gratitude (Yue et al, 2017) and anxiety (Strand et al, 2021) in which females reported higher gratitude and anxiety compared to males. Other than gender balance, future studies should include a more inclusive and diverse sampling for example, inclusion of sexual minorities as evidence has shown differential access to healthcare between heterosexual individuals and sexual minorities, especially during the pandemic, for example myths relating to homosexual individuals as the source of COVID-19 or fear of discrimination among the lesbian, gay, transgender, and queer communities as potential barriers for early diagnosis and prompt treatment for COVID-19 (Chatterjee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…17 Additionally, neuroticism has also been associated with rumination, 18 which further magnifies the negative effects of neuroticism on mental health issues. 19,20 Similar to the differences across the two sexes in the case of depressive symptoms, research has shown that women score higher on neuroticism, 21 anxiety, 22 and rumination. 23 Furthermore, the previous findings show that the effect of dispositional traits on depressive symptoms increases if other conditions, such as anxiety and rumination, are also present.…”
mentioning
confidence: 88%